Determinan Kecenderungan Kecurangan Akuntansi (Studi pada SKPK di Kota Langsa) - Teuku Muhamad Nuzul Akmal; Afrah Junita; Tuti Meutia (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This study aims to determine the effect of Internal Control Effectiveness, Compliance with Accounting Rules, and Unethical Behavior on Accounting Fraud (study on SKPK in LangsaCity). The sample selection was taken using a purposive sampling method, namely 30 SKPK in Langsa City. The type of data used is primary data and data collection is done by distributing questionnaires to 90 respondents. The data analysis methods used are validity and reliability tests, classical assumption tests, multiple linear regression tests and hypothesis testing using SPSS 22 as an analytical tool. The results of this study indicate that (1) the effectiveness of internal control has a negative and significant effect on accounting fraud, (2) compliance with accounting rules has a negative and significant effect on accounting fraud, (3) unethical behavior has a positive and significant effect on accounting expectations (4) Simultaneous Effectiveness of Internal Control, Compliance with Accounting Rules and Unethical Behavior have a significant and significant effect on the tendency of Accounting Fraud.